The Influence of Job Characteristic on Innovative Work Behavior With Work Engagement and Job Stress Being Mediating Variable ( Study on Medical Personnel at Puskesmas Kota Pontianak ) - Khodri, Muhammad B1024131015 (Jurnal Manajemen Update, 2018)
AbstractThis study aims to measure the innovative work behavior of midwives and nurses at Puskesmas Kota Pontianak by using job characteristic as independent variables and work engagement and job stress as mediating variables. Data collection using questionnaires distributed to 100 respondents with 80 questionnaires back, using census sampling technique and Likert scale used for data measurement. The classical assumption test and path analysis were used to process the data using the IBM SPSS v22 application. The results of this study indicate that job characteristics have positive and significant effect on the innovative work behavior, work engagement and job stress, while work involvement is positively and significantly related to the nature of innovative work, but job stress has no significant effect on the innovative work behavior.Keywords: Job Characteristics, Work Engagement, Job Stress, Innovative Work Behavior, Puskesmas Kota PontianakÂ REFERENCESAbdullah, M, 2015, Metode Penelitian Kuantitatif untuk Ekonomi, Manajemen, Komunikasi, Â Â Â Â Â  dan Ilmu Sosial lainnya, Penerbit Aswaja Pressindo, YogyakartaAdams, C. E. (1994). Innovative behavior in nurse executives. Nursing Management, 25(5), 44.Bakker, B. A, 2009, Buliding Engagement In The Workplace, Erasmus University Rotterdam,Department of Work and Organizational Psychology, The NetherlandsBakker, A. B, and Leiter. M. P, 2010, Work Engagement A Handbook of Essential TheoryÂ  Â Â Â Â Â Â Â Â Â  and Research, Amerika SerikatBekker, A. B, and Matthijs, P, 2010, Weekly work engagement and performance : A study Â Â Â Â Â Â Â Â Â Â Â  among starting teacher, Journal of Occupational and Organizational Psychology Â  (2010), 83, 189â€“206Badan Pusat Statistik Kota Pontiank , 2016. Pontianak Dalam Angka Tahun 2010.Â Â  Â Kota Pontianak Â : BPS Kota PontianakCohen, W.M. and Levinthal, D.A. (1990), â€œAbsorptive capacity: a new perspective on learning and innovationâ€, Administrative Science Quarterly, Vol. 35 No. 1, pp. 128-152De Jong, J., & Den Hartog, D. (2010). Measuring innovative work behaviour. Creative and Innovation Management, 19(1), 23-36.De Jong, J.P.J. (2006). Individual Innovation: The connection between leadership and employees' innovative work behavior. Paper provided by EIM Business and Policy Research in its series Scales Research Reports with number R200604. Retrieved October 24, 2007, from http://www.entrepreneurship-sme.eu/pdf-ez/R200604.pdfDe Jong, J & Den Hartog, D. (2003). Leadership as a determinant of innovative behavior. A conceptual framework. International Journal of Innovation Management.Fredrickson, B.L. (2001), â€œThe role of positive emotions in positive psychology: the broaden-and-build theory of positive emotionsâ€, American Psychologist, Vol. 56 No. 3,pp. 218-226Gibson,Ivancevich,Donnely, Organisasi dan Manajemen, Perilaku Stuktur Proses, Erlangga,Jakarta,1997Ivancevich, J.M, Konopaske, R, dan Matteson, M.T, 2006. Perilaku dan Manajemen Â Â Â Â Â Â Â Â  Organisasi. Edisi Ketujuh Jilid 1. Penerbit Erlangga, Jakarta.Janssen, O. (2005). The joint impactof perceived influence and supervisor supportiveness onemployee innovative behaviour. Journal of Occupational & Organizational Psychology, 78(4), 573-579.Jeroen P.J. de Jong,Â Deanne N. Den Hartog, (2007) "How leaders influence employees' innovative behaviour",Â European Journal of Innovation Management, Vol. 10 Issue: 1, pp.41-64Kondalkar, V.G, 2007, Organitional Behavior, New DelhiKahn, R.L., Wolfe, D.M., Quinn, R.P., & Snoek, J.D. (1964). Organizational stress: Studies in role conflict and ambiguity. New York: WileyKresnandito, A., & Fajrianthi. (2012). Pengaruh persepsi kepemimpinan transformasional terhadap perilaku inovatif penyiar radio. Jurnal Fakultas Psikologi Industri dan Organisasi UNAIR, 1(2), 96-103.Mathis, R.L, dan Jackson, J.H, 2014, Human Resource Management, Manajemen Sumber Â Â Â Â Â Â Â Â Â Â Â  Daya Manusia, Edisi 10, Penerbit Salemba Empat, JakartaMessmann, G., & Mulder, R. H. (2012). Development of a measurement instrument for innovative work behaviour as a dynamic and context-bound construct. Human Resource Development International, 15, 43â€“59.Minglong Li,Â Cathy H.C. Hsu, (2016) "A review of employee innovative behavior in services",Â International Journal of Contemporary Hospitality Management, Vol. 28 Issue: 12, pp.2820-2841,Mohd Kamel Idris, (2011) â€œOver Time Effects of Role Stress on Psychological Strain among Malaysian Public University Academicsâ€ International Journal of Business and Social Science Vol. 2 No. 9Nijenhius, Koen. 2015, Impact Factors for Innovative Work Behavior in The Public Sector. Master Thesis. University of Twente : Twente.Nasir, ABD, Muhith, A, Ideputri, M, E, 2011, Metode Penelitian Kesehatan, Penerbit Muha Â Â Â Â Â Â Â  Medika, YogyakartaPurba, Sukarman. (2009). Pengaruh Budaya Organisasi, Modal Intelektual, dan Perilaku Inovatif terhadap Kinerja Pemimpin Jurusan di Universitas Negeri Medan. Jurnal Kinerja. 13 (2): 150-167.Robbins, S.P, and Judge, T.A, 2014, Essentials of Organizational Behavior. Twelfth Edition, Â Â Â Â Â Â  United States of AmericaRobbins, S.P, and Judge, T.A, 2013, Essentials of Organizational Behavior. Fifhteenth Â Â Â Â  Edition, United States of AmericaRobbins, S. P. (2003). Organizational Behaviour, Tenth Edition. Jakarta : Salemba Empat.Riduwan, 2009, Metode dan Teknik Menyusun Proposal Penelitian, Penerbit Alfabeta, Â Â Â  BandungSunyoto, D, 2011, Analisis Penelitian Kesehatan ( Analisis Data Penelitian dengan SPSS Untuk Mahasiswa dan Praktisi Kesehatan ), Penerbit Muha Medika, YogyakartaSugiyono, 2013, Metode Penelitian Administrasi ( dilengkapi dengan metode R&D, Â Â Â Â Â Â Â Â  Alfabeta), BandungScott, S. G., & Bruce, R. A. (1994). Determinations of innovative behavior: A path model of individual innovation in the workplace. Academy of Management Journal, 37: 580-607Upasna A. Agarwal, Sumita Datta, Stacy Blakeâ€Beard, Shivganesh Bhargava, (2012) "Linking LMX, innovative work behaviour and turnover intentions: The mediating role of work engagement", Career Development International, Vol. 17 Issue: 3, pp.208-230West, M.A., and Farr, J.L. (1990) Innovation at work. In M.A. West and J.L. Farr (Eds),Â Innovation and creativity at work: Psychological and organizational strategiesÂ (pp. 3-13). Chichester, England: Wiley.Zinger, D, 2010, Employee Engagement, Powerful Sentence of Advice for Managers.Zainal, V.R, Ramly, M, Mutis. T, Arafah, W, 2009, Manajemen Sumber Daya Manusia Â Â Â  Untuk Perusahaan Dari Teori Ke Praktik, Penerbit PT. Raja Grafindo Persada, Jakarta